2017
DOI: 10.1016/j.apcatb.2016.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Probing the light harvesting and charge rectification of bismuth nanoparticles behind the promoted photoreactivity onto Bi/BiOCl catalyst by (in-situ) electron microscopy

Abstract: Highlights 1. The enhanced photoactivity on Bi/BiOCl catalyst was studied 2. Bi/BiOCl photocatalyst was prepared in TEM in situ 3. The SPR of Bi nanoparticles was confirmed by mono-EELS and simulation 4. The direct Eg value of single Bi nanoparticle was determined by mono-EELS 5. The charge transfer characteristic between Bi/BiOCl was investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…These outstanding properties make metal nanoparticles particularly attractive as co-catalysts to improve the photocatalytic performances of semiconductor photocatalysts. Very recently, metal-modified BiOX composite photocatalysts have been extensively investigated, such as Au/BiOCl, Ag/BiOBr, Bi/BiOBr and Ag/Bi/BiOCl [40][41][42][43][44][45][46]. These composite photocatalysts were shown to exhibit superior performances for dye photodegradation when compared with bare BiOX.…”
Section: Introductionmentioning
confidence: 99%
“…These outstanding properties make metal nanoparticles particularly attractive as co-catalysts to improve the photocatalytic performances of semiconductor photocatalysts. Very recently, metal-modified BiOX composite photocatalysts have been extensively investigated, such as Au/BiOCl, Ag/BiOBr, Bi/BiOBr and Ag/Bi/BiOCl [40][41][42][43][44][45][46]. These composite photocatalysts were shown to exhibit superior performances for dye photodegradation when compared with bare BiOX.…”
Section: Introductionmentioning
confidence: 99%
“…Thec apacity to analyze both surface and bulk phonon modes with an ngstrçm-scale electron probe sets monochromated EELS apart from other vibrational spectroscopies and enables direct study of optoelectronic properties at functional interfaces.F or example,F igure 5e,f shows an interface between MoS 2 and MoSe 2 in al ateral heterostructure from Tizei et al [108] Thea tomic-resolution HAADF image is shown in Figure 5e and the corresponding monochromated EELS maps of the excitonic response of MoS 2 (top) and MoSe 2 (bottom) in Figure 5f.C orrelating atomicresolution structural information by HAADF with delocalized optical and vibrational properties by monochromated EELS has allowed many fascinating results to be achieved at surfaces and interfaces in 2D materials, [108][109][110] dielectrics, [111,112] and functionalized nanoparticles. [113,114] While the dipole scattering-dominated signal collected with standard acquisition parameters results in sample-beam interactions on as cale of tens of nm, [115] high-spatial resolution vibrational spectroscopy can be enabled by angle-resolved EELS,w here signal scattered to high angles is preferentially collected. [115] This method has even been recently used to achieve atomic-resolution vibrational spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Figure e,f shows an interface between MoS 2 and MoSe 2 in a lateral heterostructure from Tizei et al . The atomic‐resolution HAADF image is shown in Figure e and the corresponding monochromated EELS maps of the excitonic response of MoS 2 (top) and MoSe 2 (bottom) in Figure f. Correlating atomic‐resolution structural information by HAADF with delocalized optical and vibrational properties by monochromated EELS has allowed many fascinating results to be achieved at surfaces and interfaces in 2D materials, dielectrics, and functionalized nanoparticles …”
Section: Emerging Stem and Eels Techniquesmentioning
confidence: 99%
“…(ii) Bi nanostructures can scatter the incident light inside the semiconductor material, thus increasing the optical absorption efficiency and photocarrier generation in this material [102,[104][105][106][119][120][121][122]. (iii) Depending on the electronic configuration of the hybrid (including potential of the photocarriers in the Bi nanostructure, location of the conduction, and valence band of the semiconductor), photocarriers, especially electrons, can flow from the Bi nanostructure to the semiconductor [94,98,103,104,[119][120][121][122][123] or the opposite [105,106,124,125]. erefore, according to different reports, Bi nanostructures can act as an electron donor (the electrons being made available for reactions at the surface of the semiconductor, Figure 12(c)) or as electron acceptor (the electrons provided by the semiconductor reacting at their surface, Figure 12(d)).…”
Section: Photocatalysismentioning
confidence: 99%
“…FDTD calculations have been done to predict the transverse and longitudinal optical cross sections of Bi nanorods with lengths up to a few hundreds of nm and their near-field enhancement [64]. Maxwell's equations solving with the volume integral equation FFT method have been used to compute the optical extinction cross section of Bi nanospheres and nanoprisms and their near-field enhancement [94].…”
Section: Optical and Plasmonicmentioning
confidence: 99%